Tantangan Pemasaran Produk Agribisnis pada UMKM Bunga Lestari: Analisis Hambatan dan Solusi - Hendra Saputra; Enzelika Rosari Putri Hutasoit; Febri Milano Sagala; Khairur Rahmah Azjahra; Najha Nawanda Zhurfiy; Patricia Wanda Sianturi; Siti Fauziah; Siti Sahira; Suastiana Anja Kelauri; Fahmi Aditiya (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Bunga Lestari MSME faces various challenges in agribusiness product marketing amidst increasingly fierce competition. This study aims to analyze the marketing challenges encountered by the MSME and formulate appropriate solutions to enhance its competitiveness. The research method employed is a qualitative approach, with data collection through direct observation and semi-structured interviews with relevant stakeholders. The results indicate that the main obstacles faced are the lack of utilization of digital media, limited market access, and minimal product innovation. These findings suggest the necessity for developing a more effective digital marketing strategy and product innovation to increase the competitiveness and sales volume of Bunga Lestari MSME in a competitive market. Thus, this study provides recommendations that can assist the MSME in addressing the existing marketing challenges.